Neurocognitive disorders: what are the prioritized caregiver needs? A consensus obtained by the Delphi method - Teddy Novais; Christelle Mouchoux; Michel Kossovsky; Lucie Winterstein; Floriane Delphin-Combe; Pierre Krolak-Salmon; V. Dauphinot (BMC, 2018)
Abstract Background The symptoms related to neurocognitive disorders (NCD) may lead to caregiver burden increase. Involving caregivers in research may be an effective way of improving the practicalities and relevance of interventions. The aim of this study was to gather opinion and gain consensus on the caregivers 'priorities, using a Delphi method and including aspects of needs in pharmaceutical dimension. Methods Observational study using a modified Delphi method. This study was conducted in the Clinical and Research Memory Center of the University Hospital of Lyon (France), between September 2015 and January 2016. The expert panel was composed of 68 informal caregivers of people with subjective cognitive decline or NCD living at home. Results Caregivers assigned a very high importance to the dimension "information needs about their relative's disease", i.e. information on the disease, the treatment and the research; and to "coping skills", i.e. skills related to emotional support, communication, relationship evolution with the relative and skills to cope with behavioural crisis, behavioural and cognitive disorders. The aspect "coping with behavioural disorders" received a high selection rate (83%). Conclusions The main needs selected can be used to design relevant interventions and give guidance to policy to support caregivers. To meet caregiver's needs, interventions should focus on information about disease and treatment and psychoeducational interventions.